: Potential for Non-Digestible Sugar Production from Cellulose and Hemicellulose using Enzymatic Hydrolysis - Sunrixon Carmando Yuansah (Hasanuddin University Food Science and Technology Study Program, 2019)
Cellulose and hemicellulose are components of lignocellulose biomass that are very abundant in nature and have the potential to be developed as one of the food ingredients, such as non-digestible sugar. The utilization of cellulose and hemicellulose in the production of non-digestible sugar can be done by biodegradation using ezymatic hydrolysis. Enzymatic hydrolysis is chosen because it is generally more environmentally friendly than chemical hydrolysis using acids or bases or physical hydrolysis which requires high energy. The enzymes used are cellulolytic and hemicellulolytic enzymes where the products produced are disaccharides such as cellobiose and oligosaccharides such as xylooligosaccharides (XOS), manooligosaccharides (MOS) and cellodextrins and other types of sugars which are cellulose and hemicellulose derivatives.